Poly(vinyl pyrrolidone)-Sodium Dodecyl Sulfate Complex as a Probe to Study the Effect of Benzyl Alcohol on Micellization Behaviour of Sodium Dodecyl Sulfate - Chen, Xiaoming; Ren, Lin (Asian Journal of Chemistry, 2013)
Poly(vinyl pyrrolidone)/sodium dodecyl sulfate complex was applied as a probe to study the effect of benzyl alcohol on micellization behaviour of sodium dodecyl sulfate. It has been found that a critical concentration (cs), exists in the relative viscosity versus benzyl alcohol concentration plot. As the benzyl alcohol concentration is less than (cs) the relative viscosity of solution containing poly(vinyl pyrrolidone)/sodium dodecyl sulfate complex increased by adding benzyl alcohol into solution successively. On the other hand, as the benzyl alcohol concentration is greater than cs, the relative viscosity of solution containing poly(vinyl pyrrolidone)/sodium dodecyl sulfate complex decreased by adding benzyl alcohol into solution. The increase and the decrease of the relative viscosity of solution containing poly(vinyl pyrrolidone)/sodium dodecyl sulfate complex in the presence of benzyl alcohol is just due to the cosurfactant and the cosolvent effect on micellization behaviour of sodium dodecyl sulfate in aqueous solution. Further experimental results indicate that cs is dependent on both sodium dodecyl sulfate and Poly(vinyl pyrrolidone) concentration.